Kedudukan Asuransi Bagi Nasabah Dalam Pembiayaan Pemilikan Rumah (Ppr) di BPD Syariah Yogyakarta - Eko Sariyekti (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
Housing Credit (KPR) Syariah is one of the alternative financing purchase of a house. Currently, almost all banks that have Sharia division one of its products is PPR Syariah. In general, they complete this financing with insurance facilities. Then, the type of research used is qualitative. With the approach of sociological law research, then as a means of data collection is by document studies (libraries) or interviews. The analysis used in this field research (field research) is descriptive qualitative with sociological normative approach. In this connection, all procedures for data analysis and processing have been discussed previously, with respect to qualitative descriptive analysis. This study concludes that the implementation of PPR BPD Syariah Yogyakarta in accordance with the MUI No.4 / DSN-MUI / 2000 fatwa about murabaha, financing agreement done in writing, using murabaha scheme. Risks in financing PPR at BPD Syariah Yogyakarta, customers are not orderly in payment of premiums and customers who have died. Solutions taken by BPD Syariah Yogyakarta in managing risk in a peaceful way (kinship) or legal path and also with insurance. While insurance in the Financing of PPR BPD Syariah insurance agreement used is akad wakalah. Insurance provided in the financing is life insurance and fire insurance.